Effect of circMAT2B on renal tubular epithelial cell damage induced by high glucose through targeting miR-103a-3p - He Chuan-mei; Xu Tong-dao; Wang Zhi; Ding Qun (Linchuang shenzangbing zazhi)
Objective To explore the effect of circMAT2B targeting miR-103a-3p on renal tubular epithelial cell damage induced by high glucose and elucidate its mechanism.Methods Human renal tubular epithelial cells HK-2 were cultured in vitro and HK-2 cells induced by high glucose for modeling cell injury（HG group）.Normally cultured HK-2 cells were recorded as Con group.And si-NC,si-circMAT2B,miR-NC,miR-103a-3p mimics, si-circMAT2B,anti-miR-NC,si-circMAT2B and anti-miR-103a-3p were transfected into HK-2 cells and then added 25 mmol/L glucose-treated cells（HG+si-NC group, HG+si-circMAT2B group, HG+miR-NC group, HG+miR-103a-3p group, HG+si-circMAT2B+anti-miR-NC group, HG+si-circMAT2B+anti-miR-103a-3p group）.Quantitative real-time polymerase chain reaction（qRT-PCR）was utilized for detecting the expression of circMAT2B and miR-103a-3p; Enzyme-linked immunosorbent assay(ELISA0 for detecting the levels of IL-6 and TNF-α;Flow cytometry for detecting apoptotic rate; Dual luciferase reporter gene experiment for examining the targeting relationship between circMAT2B and miR-103a-3p.Results As compared with Con group, the expression level of circMAT2B and apoptotic rate rose in HG group（P<0.05）,the levels of IL-6 and TNF-α spiked（P<0.05）while the expression level of miR-103a-3p dropped（P<0.05）.As compared with HG+si-NC group, the levels of IL-6 and TNF-α declined in HG+si-circMAT2B group（P<0.05）and apoptotic rate dropped（P<0.05）.circMAT2B could adsorb miR-103a-3p and target its expression.Compared with HG+miR-NC group, the levels of IL-6 and TNF-α declined in HG+miR-103a-3p group（P<0.05）while apoptotic rate dipped（P<0.05）.As compared with HG+si-circMAT2B+anti-miR-NC group, the levels of IL-6,TNF-α rose in HG+si-circMAT2B+anti-miR-103a-3p group（P<0.05）and apoptotic rate rose（P<0.05）.Conclusions An inhibition of circMAT2B expression may inhibit the secretion and apoptosis of cytoinflammatory factors by negatively regulating the expression of miR-103a-3p, thereby reducing the damage of renal tubular epithelial cells induced by high glucose.